PENGARUH PERBANDINGAN JAMUR TIRAM DENGAN BROKOLI DAN PERBANDINGAN TEPUNG TERIGU DENGAN TEPUNG UBI JALAR KUNING TERHADAP MUTU NUGGET JAMUR TIRAM (The Effect of Ratio of Oyster Mushroom with Broccoli and Ratio of Wheat Flour with Yellow Sweet Potato Flour o - Melince Situmorang; Rona J. Nainggolan; Lasma Nora Limbong (Universitas Sumatera Utara, 2017)
ABSTRACT Nugget is a food processing result of chicken, has a good flavor and favored by everyone. This research was conducted using completely randomized design with two factors, i.e ratio of oyster mushroom with broccoli (J) : (40%:60%, 50%:50%, 60% : 40%, 70%:30%) and ratio of wheat flour with yellow sweet potato flour (T) : (60%:40%, 65%:35%, 70%:30%, 75%:25%). Parameters analyzed were moisture content (%), protein content (%), crude fiber content (%), fat content (%), ash content (%), carbohydrate content (%), organoleptic value of taste, color, flavor, texture and organoleptic score of texture. The result showed that the interaction between ratio of oyster mushroom with broccoli and ratio of wheat flour with yellow sweet potato flour had a highly significant effect (P<0,01) on fat content. The increasing concentration of oyster mushroom increased the moisture content (%), protein content (%), crude fiber content (%), hedonic value texture and score value texture but decreased the fat content (%), ash content (%), and carbohydrate content (%). The increasing concentration of wheat flour increased the moisture content (%), protein content (%), hedonic value texture and score value texture but decreased the crude fiber content (%), fat content (%), ash content (%) and carbohydrate content (%). The ratio of oyster mushroom with broccoli 70%:30% and ratio of wheat flour with yellow sweet potato flour 75%:25% produced the best oyster mushroom nugget. Keywords : broccoli, oyster mushroom, oyster mushroom nugget, wheat flour, yellow sweet potato flour ABSTRAK Nugget merupakan bahan pangan hasil pengolahan daging ayam yang memiliki cita rasa enak dan digemari semua kalangan. Penelitian ini menggunakan rancangan acak lengkap (RAL) dengan 2 faktor yaitu perbandingan jamur tiram dengan brokoli (J) : (40%:60%, 50%:50%, 60% : 40%, 70%:30%) dan perbandingan tepung terigu dengan tepung ubi jalar kuning (T) : (60%:40%, 65%:35%, 70%:30%, 75%:25%). Parameter yang dianalisa meliputi kadar air (%), kadar protein (%), kadar serat kasar (%), kadar lemak (%), kadar abu (%), kadar karbohidrat (%), uji organoleptik hedoni rasa, warna, aroma, tekstur,dan skor tekstur. Hasil penelitian menunjukkan bahwa interaksi kedua perlakuan memberikan pengaruh berbeda sangat nyata (P<0,01) terhadap kadar lemak. Peningkatan jumlah jamur tiram dapat meningkatkan kadar air (%), kadar protein (%), kadar serat kasar (%), uji hedonik tekstur, dan uji skor tekstur tetapi menurunkan kadar lemak (%), kadar abu (%), dan kadar karbohidrat (%). Peningkatan jumlah tepung terigu dapat meningkatkan kadar air (%), kadar protein (%), uji hedoni tekstur, dan uji skor tekstur tetapi menurunkan kadar serat kasar (%), kadar lemak (%), kadar abu (%), dan kadar karbohidrat (%). Perbandingan jamur tiram dengan brokoli 70% : 30% dan perbandingan tepung terigu dengan tepung ubi jalar kuning 75% : 25% menghasilkan nugget jamur tiram terbaik. Kata kunci : tepung ubi jalar kuning, tepung terigu, brokoli, jamur tiram, nugget jamur tiram